Arsenic trioxide and all-trans-retinoic acid selectively exert synergistic cytotoxicity against FLT3-ITD AML cells via co-inhibition of FLT3 signaling pathways. Issue 10 (3rd October 2017) - Wang, Li-Na; Tang, Yan-Lai; Zhang, Yin-Chuan; Zhang, Zu-Han; Liu, Xiao-Jian; Ke, Zhi-Yong; Li, Yu; Tan, Hui-Zhen; Huang, Li-Bin; Luo, Xue-Qun
Abstract: FLT3-ITD mutations occur in approximately 30% of acute myeloid leukemia (AML) and are associated with a poor outcome. Currently available FLT3 inhibitors have in vitro but limited clinical activity in FLT3-ITD AML. Reports have shown that an arsenic trioxide (ATO)/all-trans-retinoic acid (ATRA) combination improves prognosis in acute promyelocytic leukemia, especially with FLT3-ITD, and ATO or ATRA alone enhances apoptosis in FLT3-ITD AML cells treated with FLT3 inhibitors, providing a rationale to investigate the role of ATO/ATRA in FLT3-ITD AML. Here, we demonstrate that an ATO/ATRA combination selectively exerts synergistic cytotoxicity against FLT3-ITD AML cell lines (MV4;11/MOLM-13). The signaling pathways affected by ATO/ATRA include FLT3/STAT5/MYC, FLT3/STAT5/E2F1, FLT3/ERK/ATF5 and FLT3/AKT/ATF5.ATF5 may function as an oncogene in FLT3-ITD AML. Our findings provide experimental evidence that supports further exploration of ATO/ATRA in FLT3-ITD AML in vivo and warrants a clinical evaluation of regimens comprising an ATO/ATRA combination.